Late presentation of posterior urethral valve: two case reports - Jesus, Carlos Márcio Nóbrega de; Trindade Filho, José Carlos de Souza; Goldberg, José (São Paulo Medical Journal, 2008)
CONTEXT: Posterior urethral valve (PUV) is a widely known condition affecting males that generally presents prenatally or at birth. PUVs have also been occasionally described in literature in cases diagnosed during adolescence or adulthood. CASE REPORT: This report presents two late PUV cases, one in a teenager and the other in an adult. Both cases had had clinical signs of urinary tract infection and obstructive urinary symptoms. The diagnoses were made by means of voiding cystourethrography and urethrocystoscopy. Endoscopic valve fulguration was the treatment chosen for both. Their follow-up was uneventful.